Previously Diagnosed Reticulum Cell Hyperplasia in Decalcified Rat Bone Marrow Stain Positive for Ionized Calcium Binding Adapter Molecule 1 (Iba1): A Monocytic/Macrophage Cell Marker. (February 2020) - Cora, Michelle C.; Janardhan, Kyathanahalli S.; Jensen, Heather; Clayton, Natasha; Travlos, Gregory S.
Reticulum cell hyperplasia (RCH) was a term used for many years by the National Toxicology Program (NTP) to describe a certain non-neoplastic bone marrow lesion of rats. Retrospective microscopic evaluation of RCH lesions and immunohistochemistry analyses were performed to reassess and further characterize these lesions. The NTP database was searched to identify femoral bone marrow specimens diagnosed with RCH from 1981 to 2014 (n = 254). The diagnosis last occurred in 2003, after which the term "cellular infiltration" was used. Eighty-three RCH slides, spanning 22 years, representing 34 different chemicals, were selected for microscopic review, and a subset (23) was chosen for ionized calcium binding adapter molecule 1 (Iba1) immunohistochemical staining; initial investigations revealed Iba1 worked as a macrophage marker on decalcified tissue. The following diagnoses were made upon reevaluation: 36 were consistent with cellularity increased, macrophage, 22 with histiocytic sarcoma, 8 with increased myeloid cells, 4 with autolysis, and 13 were normal appearance. All 23 RCH lesions stained positive for Iba1. Fifty-eight of 83 bone marrows previously diagnosed with RCH are consistent morphologically and immunohistochemically with cells of histiocytic origin. These results will help with interpretation of historical data and demonstrates that Iba1 can be used in decalcified bone marrow sections.